Analysis and interpretation of a unique Arabic finger ring from the Viking Age town of Birka, Sweden. Issue 2 (23rd February 2015) - Wärmländer, Sebastian K.T.S.; Wåhlander, Linda; Saage, Ragnar; Rezakhani, Khodadad; Hamid Hassan, Saied A.; Neiß, Michael
Summary In this work we used non‐destructive SEM imaging and EDS analysis to characterize the material composition of an Arabic finger ring, which was found in a 9th c. woman's grave at the Viking Age (A.D. 793–1066) trading center of Birka, Sweden. The ring is set with a violet stone inscribed with Arabic Kufic writing, here interpreted as reading "il‐la‐lah", i.e. "For/to Allah". The stone was previously thought to be an amethyst, but the current results show it to be coloured glass. The ring has been cast in a high‐grade silver alloy (94.5/5.5 Ag/Cu) and retains the post‐casting marks from the filing done to remove flash and mold lines. Thus, the ring has rarely been worn, and likely passed from the silversmith to the woman buried at Birka with few owners in between. The ring may therefore constitute material evidence for direct interactions between Viking Age Scandinavia and the Islamic world. Being the only ring with an Arabic inscription found at a Scandinavian archaeological site, it is a unique object among Swedish Viking Age material. The technical analysis presented here provides a better understanding of the properties and background of this intriguing piece of jewelry. SCANNING 37:131–137, 2015. © 2015 Wiley Periodicals, Inc.